Low complement levels are related to poor obstetric outcomes in women with obstetric antiphospholipid syndrome. The EUROAPS Registry Study Group. (May 2023) - Esteve-Valverde, Enrique; Alijotas-Reig, Jaume; Belizna, Cristina; Marques-Soares, Joana; Anunciacion-Llunell, Ariadna; Feijóo-Massó, Carlos; Sáez-Comet, Luis; Mekinian, Arsene; Ferrer-Oliveras, Raquel; Lefkou, Elmina; Morales-Pérez, Stephanie; Hoxha, Ariel; et al.
Abstract: Introduction: Obstetric antiphospholipid syndrome (OAPS) is an autoimmune disease related to antiphospholipid antibodies (aPL) with primaryinflammatory injury followed by clot cascade activation and thrombus formation. Complement system activation and their participation in aPL-related thrombosis is unclosed. Methods: We haveanalysed adverse pregnancy outcomes (APO) related to low complement (LC) levels in a cohort of 1048 women fulfilling classification criteria for OAPS. Results: Overall, 223 (21.3%) women presented LC values, during pregnancy. The length of pregnancy was shorter in OAPS women with LC compared to those with normal complement (NC) (median: 33 weeks, interquartile range: [24–38] vs. 35 weeks [27–38]; p = 0.022). Life new-born incidence was higher in patients with NC levels than in those with LC levels (74.4% vs. 67.7%; p = 0.045). Foetal losses were more related to women with triple or double aPL positivity carrying LC than NC values (16.3% vs. 8.0% NC; p = 0.027). Finally, some placental vasculopathies were affected in OAPS patients with LC as late Foetal Growth Restriction (FGR >34 weeks) rise to 7.2% in women with LC vs. 3.2% with NC (p = 0.007). Discussion: Data from our registry indicate that incidence of APO was higher in OAPS women with LC levels and some could be reverted by the correct treatment. Highlights: Complement system could play a key role in aPL-related poor obstetric outcomes. Mechanisms through complement mediates OAPS complications are still unknown. Low plasma C3 and C4 were predictors of lower birth weight and premature delivery. Hypocomplementemia is associated with deposition on the placental tissue. Low levels of circulating complement may be used to identify risk APS pregnancies.